IDENTIFICATION OF INDUSTRIAL HAZARDOUS WASTES IN TEHRAN AND VARIOUS METHODS OF THEIR DISPOSAL - M.Asadi;D. Faezy Razy; M. Vojdany (Tehran University of Medical Sciences, 1993)
There are enormous quantities of unknown composition of hazardous wastes in Tehran without any control, safe disposal and treatment. This study was done to identify hazardous wastes and to control this wastes by establishing a treatment, storage and disposal facility. According to available statistics there are 4461 different industries in Tehran, out of which sample were chosen each having over ten employees. From the data collected, the quantity of liquid, solid and semi-solid industries hazardous wastes was 149050 tons all together, Of the mentioned total waste, a ratio of 46.64% is toxic, 30.84% is corrosive, 1.73% is ignitable and 20.79% of the waste shows other characteristics. About 40.83% of the produced waste is transported to the municipality site, 1.72% is incinerated against sanitary regulations, 1.96% is recovered of recycled, 37.19% is landfilled in place other than municipality site and some other wastes are disposed by unauthorized methods.